2017
DOI: 10.17159/2223-0386/2017/n17a3
|View full text |Cite
|
Sign up to set email alerts
|

Student protest and the culture of violence at African universities: An inherited ideological trait

Abstract: Since the advent of independence in African countries, education generally focused on transforming these nations and redressing the ills of colonialism. Education in countries like Ghana, and Kenya, amongst others aimed at redressing the colonial legacy by creating a new world order marked by equality, mutual benefits and participation. However, this drive for equality, mutual benefits and participation has been beset by several challenges, ranging from access to funding. The recent and most devastating challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
(54 reference statements)
0
19
0
2
Order By: Relevance
“…The constant call for decolonisation in the South African higher education system is a clear indicator of the failure of the curriculum to produce against the backdrop of hegemonic power structures. To this effect, responsiveness within the context of decolonisation is only possible if curricula charges such as responsibilities, consciousness, commitments and projects are rid of ideological nuances that make them unhealthy for academic discussion (Fomunyam, 2014;Fomunyam, 2017b). Higher education in South Africa has amongst other things three intrinsic objectives; value for money, fitness for purpose and transformation (Fomunyam, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The constant call for decolonisation in the South African higher education system is a clear indicator of the failure of the curriculum to produce against the backdrop of hegemonic power structures. To this effect, responsiveness within the context of decolonisation is only possible if curricula charges such as responsibilities, consciousness, commitments and projects are rid of ideological nuances that make them unhealthy for academic discussion (Fomunyam, 2014;Fomunyam, 2017b). Higher education in South Africa has amongst other things three intrinsic objectives; value for money, fitness for purpose and transformation (Fomunyam, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…He traced this to the long period of military rule and the culture of institutionalized violence. This also has been agreed by Fomunyam (2017) who attributed violence at African universities to the "an inherited ideological trait" and indicated that the process would continue in the future unless careful actions and policies are taken to ensure transformation and decolonization in those countries.…”
Section: Introductionmentioning
confidence: 89%
“…Over the course of their history, African universities have had to contend with many crises, and they have learnt to quickly adapt to ensure that conditions for teaching and learning, as well as student development and support, continue. Political turmoil, economic downturns, fiscal austerity, social conflicts, staff and student strikes, virus outbreaks and even civil wars have forced universities into circumstances that require difficult decisions in a context of great uncertainty and complexity (Fomunyam, 2017). While such disaster periods and events often have deeply disruptive effects on the university community, they tend to last a limited time only.…”
Section: A Global Pandemic With Local Realitiesmentioning
confidence: 99%